Dielectric spectroscopy as a condition monitoring technique for cable insulation based on crosslinked polyethylene. (July 2015) - Linde, E.; Verardi, L.; Fabiani, D.; Gedde, U.W.
Abstract: Dielectric spectroscopy was evaluated as a condition monitoring technique for aged polyethylene electrical insulation in nuclear power plants. Bare core insulations of crosslinked polyethylene were aged at 55 and 85 °C under exposure to 60 Co γ-radiation at different dose rates (0.42, 0.76 and 1.06 kGy h −1 ) to different total doses. The samples were studied by dielectric spectroscopy and tensile testing, and the crystallinity, mass fraction of soluble component and density were determined. The oxidation profiles along the depth of the insulations were assessed by infrared microscopy. The aged samples showed an increase in both the real and imaginary parts of the dielectric permittivity over the whole frequency range studied, an increase in the mass fraction of soluble component and in the material density, and a decrease in the strain-at-break. The imaginary part of the dielectric permittivity at 100 kHz increased in a linear fashion with increasing material density, the latter being strictly related to the extent of oxidation of the material according to infrared spectroscopy and differential scanning calorimetry. The generic relationship between the imaginary part of the permittivity and the density included all the data obtained under different ageing conditions. The results suggest that dielectric spectroscopy can be used for in-situ measurements of the degree of oxidation of polyethylene cables, in order to obtain information about the condition of the cable insulation to enable the remaining lifetime to be predicted.